Exploring determinants of health-seeking behavior among coastal communities: A qualitative study - Rahman Hossain; Ayesha Akter (Science Center Group, 2026)
Background: Health-seeking behavior remains a critical determinant of health outcomes in coastal communities, where limited access to primary health care often delay timely utilization of health services. Coastal populations frequently rely on subjective illness appraisal and informal care pathways, which may increase health risks and exacerbate inequities in health service utilization. Objective: This study aimed to explore the determinants of health-seeking behavior among coastal communities from a qualitative perspective to inform community nursing and primary health care practices. Methods: A qualitative study using an interpretive descriptive approach was conducted among adults living in coastal communities in Bangladesh. Participants were selected through purposive sampling based on their experience seeking health care services. Data were collected through in-depth, semi-structured interviews conducted in the local language. Thematic analysis was applied using an inductive approach to identify key patterns and determinants of health-seeking behavior. Trustworthiness was ensured through member checking, audit trails, and reflexive analysis. Results: The analysis revealed four major themes influencing health-seeking behavior: illness perception and symptom appraisal, accessibility and structural barriers, sociocultural and household influences, and health system experiences. Participants often delayed seeking formal care due to normalization of symptoms, financial limitations, transportation difficulties, and reliance on family decision-making. Positive or negative prior experiences with health services strongly shaped future care-seeking behavior. These determinants interacted dynamically, resulting in fragmented and non-linear care-seeking pathways. Conclusion : Health-seeking behavior in coastal communities is influenced by multidimensional and context-specific determinants that extend beyond individual decision-making. Community nursing and primary health care interventions should emphasize culturally sensitive health education.